Redescription, molecular characterisation and taxonomic re-evaluation of a unique African monitor lizard haemogregarine Karyolysus paradoxa (Dias, 1954) n. comb. (Karyolysidae). Issue 1 (December 2016) - Cook, Courtney; Netherlands, Edward; Smit, Nico
Abstract Background Within the African monitor lizard family Varanidae, two haemogregarine genera have been reported. These comprise five species ofHepatozoon Miller, 1908 and a species ofHaemogregarina Danilewsky, 1885. Even though other haemogregarine genera such asHemolivia Petit, Landau, Baccam & Lainson, 1990 andKaryolysus Labbé, 1894 have been reported parasitising other lizard families, these have not been found infecting the Varanidae. The genusKaryolysus has to date been formally described and named only from lizards of the family Lacertidae and to the authors' knowledge, this includes only nine species. Molecular characterisation using fragments of the 18S gene has only recently been completed for but two of these species. To date, threeHepatozoon species are known from southern African varanids, one of theseHepatozoon paradoxa (Dias, 1954) shares morphological characteristics alike to species of the family Karyolysidae. Thus, this study aimed to morphologically redescribe and characteriseH. paradoxa molecularly, so as to determine its taxonomic placement. Methods Specimens ofVaranus albigularis albigularis Daudin, 1802 (Rock monitor) andVaranus niloticus (Linnaeus in Hasselquist, 1762) (Nile monitor) were collected from the Ndumo Game Reserve, South Africa. Upon capture animals were examined for haematophagous arthropods. Blood was collected, thin blood smears prepared, stained with Giemsa, screened and micrographs of parasites captured. Haemogregarine morphometric data were compared with the data for named haemogregarines of African varanids. Primer set HepF300 and HepR900 was employed to target a fragment of the 18S rRNA gene and resulting sequences compared with other known haemogregarine sequences selected from the GenBank database. Results Hepatozoon paradoxa was identified infecting two out of eight (25 %)V. a. albigularis and a single (100 %)V. niloticus examined. Phylogenetic analyses revealed thatH. paradoxa clustered with the 'Karyolysus ' clade, and not with those of reptilianHepatozoon spp. Conclusions In addition to this being the first morphological and molecular characterisation of a haemogregarine within the African Varanidae, it is the first report of a species ofKaryolysus infecting the monitor lizard family. Furthermore, this constitutes now only the third described and namedKaryolysus species for which there is a nucleotide sequence available.